Endoscopic management of acute oesophageal variceal bleeding within 12 hours of admission is superior to 12–24 hours. Issue 3 (3rd July 2021) - Mousa, N; Abdel-Razik, A; Sheta, T; G Deiab, A; Habib, A; Diasty, M; Eldesoky, A; Taha, A; Mousa, E; Yassen, A; Fathy, A; Elgamal, A
ABSTRACT: Background: Acute oesophageal variceal haemorrhage (AOVH) is a medical emergency. The American Association for the Study of Liver Diseases recommends endoscopy management as soon as possible and not more than 12 hours after presentation. The United Kingdom guidelines recommended endoscopy for unstable patients with severe acute upper gastrointestinal bleeding immediately after resuscitation and within 24 hours of admission. We aimed to evaluate the outcome of endoscopic management of AOVH in less than 12 hours compared to 12–24 hours post admission. Methods: 297 patients with AOVH were divided into groups depending on the timing of the endoscopic management: 180 within 12 h of admission and 117 patients at 12–24 hours of admission. Routine clinical and laboratory data were collected. Results: Compared to patients with endoscopic management at 12–24 hours (mean 16 hours), patients with endoscopic management within 12 hours (mean 8.3 hours) of admission had fewer hospital stay days (P = 0.001), significant reduction of ammonia levels (P < 0.0001) and significant improvement in associated hepatic encephalopathy grade 25 (p = 0.048). There were no major clinical events in the 12-hour group, but 8 events in the 12–24 hour group (p < 0.01). Conclusion: Endoscopic management of acute variceal bleeding within 12 hours of admission is superior to endoscopic management at 12–24 hours of admission regarding reduction of hospital stay, ammonia levels, correction of hepatic encephalopathy, re-bleeding and mortality rate, hence, reducing the cost of treatment benefiting patient satisfaction and improving hospital bed availability.